SOLAR CHARGER FOR MOBILE PHONE BATTERY - Чорна, Ю.; Долотов, Ю.; Маслюкова, З. (Science-based technologies, 2010)
A circuit diagram and design of autonomous mobile charger for mobile phones that uses solar energy. Defined voltage and current, which must be obtained from photoconverters to ensure reliable operation of a solar charger. The methodology of choice grade solar photoconverters and basic elements of electric circuit and the characteristic of their work